INFLAMMATORY BOWEL DISEASE: IMPACT ON SCORES OF QUALITY OF LIFE, DEPRESSION AND ANXIETY IN PATIENTS ATTENDING A TERTIARY CARE CENTER IN BRAZIL - CALIXTO,Raquel Pellizzari (2018)
ABSTRACT BACKGROUND: Inflammatory bowel disease frequently affects patients at working age, compromising their quality of life in several levels: physical, psychological, familial and social. Few studies have evaluated the impact of Inflammatory bowel disease on quality of life, anxiety and depression in Brazilian patients. OBJECTIVE: Evaluate quality of life and its correlation with psychological aspects of patients with inflammatory bowel disease through the Inflammatory Bowel Disease Questionnaire and Hospital Anxiety and Depression Scale. METHODS: Cross-sectional study; Inflammatory Bowel Disease Questionnaire, Short Form-36 and Hospital Anxiety and Depression Scale were applied to consecutive outpatients in a tertiary referral center for inflammatory bowel disease. Harvey-Bradshaw Index and Truelove scores were used to evaluate Crohn’s disease and ulcerative colitis activity. Sample calculation: 113 patients for a significance level of 5%, power of 90% and a correlation coefficient of at least 0.3 between scales. Statistical analysis: Student-t test, Pearson and Spearman correlations. RESULTS: One hundred twenty patients participated in the study; mean age: 41.7 years; female: 58.3%; Crohn’s Disease: 69 patients. No low scores for quality of life were found across the four Inflammatory Bowel Disease Questionnaire domains; the Short Form-36 showed low scores in physical limitations (47.2±42.4) and emotional aspects (49.8±43.4); Hospital Anxiety and Depression Scale score presented a mean of 9.5±2.7 for anxiety and 8.7±2.0 for depression. Quality of life was decreased and Hospital Anxiety and Depression Scale did show increased indices of anxiety and depression, in both diseases only when clinically active. CONCLUSION: Inflammatory Bowel Disease Questionnaire and Hospital Anxiety and Depression Scale showed that outpatients of a tertiary care center for inflammatory bowel disease in Brazil presented good quality of life. The worst quality of life was associated with the intensity of the disease activity.